2009
DOI: 10.1038/nature07884
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of NEDD8-activating enzyme as a new approach to treat cancer

Abstract: The clinical development of an inhibitor of cellular proteasome function suggests that compounds targeting other components of the ubiquitin-proteasome system might prove useful for the treatment of human malignancies. NEDD8-activating enzyme (NAE) is an essential component of the NEDD8 conjugation pathway that controls the activity of the cullin-RING subtype of ubiquitin ligases, thereby regulating the turnover of a subset of proteins upstream of the proteasome. Substrates of cullin-RING ligases have importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

82
1,970
9
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,725 publications
(2,067 citation statements)
references
References 46 publications
82
1,970
9
6
Order By: Relevance
“…To confirm that the binding between Fbxl17 and Sufu was not due to spurious interaction due to Fbxl17 overexpression, we isolated endogenous Sufu after treating cells with an inhibitor of NAE (Nedd8‐activating enzyme) (MLN4924) (Soucy et al , 2009). This treatment blocks cullin neddylation required for the activity of SCF ubiquitin ligases (Ohh et al , 2002).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that the binding between Fbxl17 and Sufu was not due to spurious interaction due to Fbxl17 overexpression, we isolated endogenous Sufu after treating cells with an inhibitor of NAE (Nedd8‐activating enzyme) (MLN4924) (Soucy et al , 2009). This treatment blocks cullin neddylation required for the activity of SCF ubiquitin ligases (Ohh et al , 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The MLN4924 induced toxicity in proliferating cells, is mainly due to the resulting S-phase arrest 11 . We tested the effect of p53 and RPL11 knockdown on cell cycle progression ( The opposite effect was observed upon RPL11 knockdown, which reduced both the MLN4924-induced accumulation of cells in S-phase and cytotoxicity (Fig.…”
Section: Differential Roles Of Rpl11 and P53 In Mln4924-induced Accummentioning
confidence: 99%
“…This knowledge combined with the fact that the inhibitor of the proteasome, bortezomib (Velcade ® ), is used for the treatment of various types of myeloma and lymphoma, prompted development of specific inhibitors of the NEDD8 machinery 4,10 . MLN4924 is a small molecule that specifically inhibits the NEDD8 pathway 11,12 . Treatment of tumour cells with MLN4924 can induce apoptosis, and in vivo MLN4924 shows anti-tumour activity in mice harbouring human xenografts for solid and hematologic tumours 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies demonstrated that cullin neddylation is required for efficient ubiquitylation and/or turnover of CRL substrates in vivo, which has been borne out through the development of MLN4924, a small-molecule inhibitor of NAE [14,[48][49][50]. Inhibition of CRL activity by MLN4924 results in accumulation of a host of CRL targets [14,43,51,52].Structural and biochemical studies revealed a complex mechanism underlying cullin neddylation that involves dual E3 activity and co-translational modification of neddylation E2s to strongly activate the transfer of NEDD8 to the cullin [39,44,53,54]. Early studies indicated that UBC12 can neddylate CUL1 in vitro in a manner that requires RBX1 [55][56][57] For simplicity, therefore, we refer to Cdc53 as yeast CUL1 throughout.…”
mentioning
confidence: 99%